(untitled) (Annals of Medical Research, 2021)
Aim: Ocular allergy is an ocular surface disease deteriorates the patient’s quality of life. This situation continues and repeats inflammation via allergen contacts. Inflammation disrupted the tear film instability and may lead to dry eye. The aim of our study is to investigate concurrently appearing signs and symptoms of dry eye in a group of patients with symptomatic allergic conjunctivitis.Material and Methods: To be evaluated 141 patients with ocular allergy and 138 patient without ocular allergy in terms of dry eye symptoms and signs by Oxford scheme, OSDI scores, Break up time (BUT) and Schirmer test.Results: There was a statistically significant difference was detected between the dry eye scores of the two groups.Conclusion: It may be related that ocular allergy and dry eye. Because of this relation, patients have ocular allergy evaluated in terms of dry eye simultaneously.Keywords: Dry eye; allergic conjunctivitis; break up time; schirmer; osdi.